Oral reading fluency and sentence processing tasks among primary one pupils in S.K. Raso / Barbara Demit Anak Lanyau - Lanyau, Barbara Demit (2015)
The aim of this thesis was to find out relationship between passage oral-reading duration with word-reading behaviours, investigate effectiveness of sight words intervention on oral reading fluency (ORF) and examine tasks of sentence processing (SP) the participants carried out during the fluency assessment. This thesis first investigated students' ORF after a series of whole-class sight word instruction and small-group sight word intervention in addition to whole-class sight word instruction. Learning instructions and intervention activities were followed by reading assessment segments. Second set of similar study were applied following completion of previous set. Quantitative analysis were made on students' word-reading measures: error, accuracy, self-correction rate and passage-reading measures: reading times. There were high correlations between wordreading measures with passage-reading measure. Reading durations were regarded as students' ORF. Norm-referenced tests and criterion-referenced tests analysed pupils' ORF changes Their reading times were charted for A-B-A single subject research designs. Sight words intervention in this study helped increased students' ORF. Their reading speed increased overtime. From field notes case study, the proposed SP among students involved tangible and intangible tasks. Conclusion addressed pedagogical implication of this research that includes efficiency of sight words skills, story passage skills and continuous reading fluency assessment.